Negative impact of porcine circovirus type 2 infection on the efficacy of classical swine fever vaccine in a field farm - KUWATA, Keisuke; OTSU, Keko; INOHA, Shuko; KIMURA, Yoko; AOKI, Hiroshi; SAKODA, Yoshihiro (Journal of Veterinary Medical Science, 2025)
Porcine circovirus type 2 (PCV2) induces wasting and immunosuppression in pigs and is widely transmitted in pig farms worldwide. Classical swine fever (CSF) is a particularly important contagious disease in pigs. In CSF-endemic areas, such as Japan, thorough vaccination is performed, and effective use of the CSF vaccine is important to prevent outbreaks. This study investigated the impact of PCV2 infection on the immune response to CSF vaccines in field farms. The mortality rate of fattening pigs on the farm was investigated, and pig sera were used to measure the PCV2 viral load and neutralizing antibody titer of CSF as indicators of CSF vaccine efficacy. Results indicated a sharp increase in mortality rate, PCV2 detection rate reaching 100%, and high viral load, whereas CSF antibody titers were significantly lower in the fattening pig herd. After PCV2 inactivated vaccination was initiated, the mortality rate, PCV2 detection rate, and viral load in fattening pigs decreased, and CSF antibody titers also improved. Furthermore, there was a correlation between higher PCV2 viral load and lower CSF antibody titers in this farm. In contrast, other PCV2-vaccinated farms had higher CSF antibody levels. These results indicate that PCV2 infection negatively affects the efficacy of CSF vaccines, and the control of PCV2 in field farms is important.